Desarrollo de una propuesta para el diseño conceptual de la producción de un edulcorante a base de yacón (2019)
In this project the yacon is studied, which is a tuber that stores carbohydrates in the form of Fructooligosaccharides and in free sugars. The characterization of the root is carried out to determine the percentage of humidity, percentage of ashes, pH, density, amount of FOS the results obtained from contents in this project is 86.6%, 0.513%, 6.71, 1.032 g / mL, 37.9 g / mL extract respectively, these values obtained are necessary to control the production of the sweetener. Since having a reserve root this accumulates water in 70% to 93% and carbohydrates such as fructans and simple sugars between 40% and 70%. In the experimental part of the production of the sweetener, the factor that most affects the production of fructose is selected, which in this case is the type of acid since it has a statistical significance in the response variable, obtaining the best results with sulfuric acid with a value of 0.000745 g / mL extract compared to those obtained with hydrochloric acid with a value of 0.00045 g / mL extract. That said, the yacon is totally suitable to produce sweetener since having large amounts of fructooligosaccharides (FOS) is classified as a beneficial prebiotic for human health. When carrying out the design for the extraction of the sweetener, an escalation of the test was carried out that obtained the best results in the experimental part considering the amount of sweetener required with a value of 400 kg / month, being that 12.80 kg / h of sweetener to meet the demand established by the institution where 7.2 kg / h of yacon, 0.0425 kg / h of sulfuric acid and 0.013 kg / h of calcium hydroxide are required.